Electro arthrography: Recording Electrical Potentials At the Elbow Joint - Divakaran, Sindu; Janney J, Bethanney; R, Priyanga; Jalagam, Sindoora; R C, Ramya; R, Shakthi (International Journal of Engineering and Technology, 2018)
Electroarthrography (EAG) is a recent technology proposed to detect cartilage degradation. It is used to record electrical potentials generated on the surface of elbow while the joint undergoes compressive loading. The aim of this work is to understand the generation of EAG signals and to differentiate between the healthy and unhealthy elbow based on its cartilage degradation. It has been found that EAG signals originate from the cartilages based on the simulated and measured potential values distributions. Unhealthy cartilages produce varying current density with specific potential distribution. EAG signals can be used as a clinical tool to diagnose bone and cartilage degradation.Â